2022
DOI: 10.17102/cnr.2022.71
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary inventory of native natural enemies of the new pest; Fall armyworm (Spodoptera frugiperda)

Abstract: Fall Armyworm (Spodoptera frugiperda), which began to spread in Bhutan in recent years, is a highly destructive pest of maize that is native to the Americas. Due to the limited information available for developing sustainable management options for the new pest, current management practices are largely chemical-dependent. For use as a biological control option, we present a preliminary list of native natural enemies associated with Fall Armyworm that is collected from infested maize fields in west-central Bhut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This species has been reported as an important predator in other parts of the world. An inventory of the native natural enemies in Bhutan, P. versicolor was among 48 other natural enemies associated with the pest (Dorji et al, 2022). Southon et al (2019) also reported on the effectiveness of this predatory wasp in managing the fall armyworm and the sugarcane borer Diatraea saccharalis (F) (Lepidoptera: Crambidae).…”
Section: Potential Of Using Biological Controlmentioning
confidence: 99%
“…This species has been reported as an important predator in other parts of the world. An inventory of the native natural enemies in Bhutan, P. versicolor was among 48 other natural enemies associated with the pest (Dorji et al, 2022). Southon et al (2019) also reported on the effectiveness of this predatory wasp in managing the fall armyworm and the sugarcane borer Diatraea saccharalis (F) (Lepidoptera: Crambidae).…”
Section: Potential Of Using Biological Controlmentioning
confidence: 99%